Effect of circuit breaker reclosure time on the performance of a power system: article / Tuan Affindi Tuan Abdullah - Tuan Abdullah, Tuan Affindi (Universiti Teknologi MARA (UiTM), 2008)
The magnitude and duration ofrestrikes upon the reclosure of the terminals of a circuit-breaker is important as failure to close at the right time may lead to detrimental effect to the power system in which the circuit breaker reside. For the purpose of demonstrating the operation of the circuit breaker to high voltage engineering students, this project is undertaken. A model of the power system in which the circuit breaker resides is designed based on the IEC standard. At the source side of the circuit breaker a circuit is present for reproducing a (2-parameter IEC) transient recovery voltage, while the RLC circuit at the line side represents a short transmission line that is short circuited. An single-shot pulse generator represents the source of surge. The simulation was conducted using MATLAB' Simulink (MLS). The performance of the power system is analysed in terms of the magnitude and duration of the restr iking voltages. By comparing the switching time made at various points on the sinusoidal power source, the importance of correct switching time can be appreciated